2012
DOI: 10.1177/0954407011430182
|View full text |Cite
|
Sign up to set email alerts
|

Classification and analysis of electric-powered lateral torque-vectoring differentials

Abstract: An electric-powered lateral torque-vectoring differential utilizes the output torque of an electric motor for generating the torque difference between the right and the left wheels. Compared with conventional torque-vectoring differentials which utilize the slipping clutch or brake for torque vectoring, electric-powered lateral torque-vectoring differentials have advantages, namely the response and the control accuracy of the torque difference. However, an electric-powered lateral torque-vectoring differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…(5) The energy efficiencies of MLTD at left turn are very close to those at straight driving in the mid/high speed range, while those at right turn are still about 95% lower mainly due to unavoidable loss of power recirculation. (6) The energy deficiencies at right turn may be paid off by moderately cutting down the rolling resistance of tire by 11.1%, e.g., reducing vehicle mass of 1600 kg by about 200 kg, with the superior cornering performances still held using lateral torque vectoring. (7) Conclusively, the newly proposed MLTD possesses greater potential to enhance energy efficiency and driving range of electric vehicles without trading off against its desirable cornering performance and safe handling, and is thus worthy of further development.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) The energy efficiencies of MLTD at left turn are very close to those at straight driving in the mid/high speed range, while those at right turn are still about 95% lower mainly due to unavoidable loss of power recirculation. (6) The energy deficiencies at right turn may be paid off by moderately cutting down the rolling resistance of tire by 11.1%, e.g., reducing vehicle mass of 1600 kg by about 200 kg, with the superior cornering performances still held using lateral torque vectoring. (7) Conclusively, the newly proposed MLTD possesses greater potential to enhance energy efficiency and driving range of electric vehicles without trading off against its desirable cornering performance and safe handling, and is thus worthy of further development.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Thereby, the optimal longitudinal forces of wheels applied through the TVD of each drivetrain are attained by analyzing the dynamic limits of the vehicle so that the cornering ability in terms of the maximum lateral acceleration can be found. Kato et al [6] carried out a kinematics analysis on an electric-powered lateral torque vectoring differential (E-TVD) with two degrees of freedom and five elements, consisting of a single electric motor, the first planetary gear, and the second planetary gear. The differential can be classified and characterized by analyzing the relationship between torque and speed of each component using speed diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Direct yaw moment control systems are categorized as differential braking and differential traction systems. [3][4][5] Differential braking systems are widely used in today's cars and have a positive impact on vehicle safety. However, differential braking systems have some weaknesses; for instance, their actuation can disturb the driver and, more importantly, can lead to longer stopping distances during severe braking-in-aturn manoeuvres.…”
Section: Introductionmentioning
confidence: 99%
“…Mitsubishi S-AWC, Honda SH-AWD and ZF Torque Vectoring). Studies of the dynamics and control logic of TVDs have been previously reported, [3][4][5][6][7][8][9][10][11][12][13][14] and the principles of operation have already been explained in detail.…”
Section: Introductionmentioning
confidence: 99%